Nursing students' clinical performance and professional self-concept (Bangladesh Journal of Medical Science, 2016)
Objective: Nursing professional self-concept is nurses' internalized values and beliefs and the manner they affect their thoughts and behavior. The questions of how nursing students see themselves and what qualities interest them are of great importance. The present study aims to determine the correlation between clinical performance and nursing students professional self-concept. Materials and Method: The present cross-sectional-analytical study was conducted on 86 nursing students at Jahrom universities of medical sciences. The study data were collected using a questionnaire which consisted of 6-Dimension Scale of Nurse Performance (6-DSNP) and Nurse Self-Concept Questionnaire (NSCQ). The data analyzed using descriptive and inferential statistics. Results: The nursing students clinical performance and professional self-concept scores were 2.94±1.45 and 5.46±1.11. Pearson correlation coefficient revealed a significant correlation between the students clinical performance and professional self-concept. Total 6-DSNP score were significantly related to two of the dimensions of NSCQ: Nursing care and communication (p